Clinical Outcomes of the Marginal Ulcer Bleeding after Gastrectomy: As Compared to the Peptic Ulcer Bleeding with Nonoperated Stomach. (3rd December 2012) - Chung, Woo Chul; Jeon, Eun Jung; Lee, Kang-Moon; Paik, Chang Nyol; Oh, You Suk; Lee, Yang Woon; Kim, Sang Bae; Jun, Kyong-Hwa; Chin, Hyung Min
Abstract : Background . Marginal ulcer is a well-known complication after gastrectomy. Its bleeding can be severe, but the severity has rarely been reported. We aim to evaluate the clinical outcomes of marginal ulcer bleeding (MUB) as compared to peptic ulcer bleeding (PUB) with nonoperated stomach. Methods . A consecutive series of patients who had nonvariceal upper gastrointestinal bleeding and admitted to the hospital between 2005 and 2011 were retrospectively analyzed. A total of 530 patients were enrolled in this study, and we compared the clinical characteristics between 70 patients with MUB and 460 patients with PUB. Results . Patients with MUB were older (mean age: 62.86 ± 10.59 years versus 53.33 ± 16.68 years, P = 0.01 ). The initial hemoglobin was lower (8.16 ± 3.05 g/dL versus 9 .38 ± 2 .49 g/dL, P = 0.01 ), and the duration of admission was longer in MUB (7 .14 ± 4 .10 days versus 5 .90 ± 2 .97 days, P = 0.03 ). After initial hemostasis, the rebleeding rate during admission was higher (16.2% versus 6.5%, P = 0.01 ) in MUB. However, the mortality rate did not differ statistically between MUB and PUB groups. Helicobacter pylori -positive rate with MUB was lower than that of PUB (19.4% versus 54.4%, P = 0.01 ). Conclusions . Clinically, MUB after gastrectomy is more severe than PUB with nonoperated stomach. Infection with H. pylori might not appear to play an important role in MUB after gastrectomy.